Metabolic Alterations in Inherited Cardiomyopathies - Sacchetto, Claudia (J Clin Med, 2019)
The normal function of the heart relies on a series of complex metabolic processes orchestrating the proper generation and use of energy. In this context, mitochondria serve a crucial role as a platform for energy transduction by supplying ATP to the varying demand of cardiomyocytes, involving an intricate network of pathways regulating the metabolic flux of substrates. The failure of these processes results in structural and functional deficiencies of the cardiac muscle, including inherited cardiomyopathies. These genetic diseases are characterized by cardiac structural and functional anomalies in the absence of abnormal conditions that can explain the observed myocardial abnormality, and are frequently associated with heart failure. Since their original description, major advances have been achieved in the genetic and phenotype knowledge, highlighting the involvement of metabolic abnormalities in their pathogenesis. This review provides a brief overview of the role of mitochondria in the energy metabolism in the heart and focuses on metabolic abnormalities, mitochondrial dysfunction, and storage diseases associated with inherited cardiomyopathies.